2020
DOI: 10.1101/2020.08.06.240523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioactivity of Aqueous Extract of Pulp ofCrysophyllum albidium(G. Don-Holl.) on Isoproterenol Treated Albino Rats

Abstract: Cardiovascular disorder is one of the causes of death globally. Quite a number of medicinal plants have been demonstrated to possess and exhibit beneficial effects on cardiovascular system throuhg their antioxidant properties. The study investigated the in vivo antioxidant properties of aqueous C. albidium pulp extract on isoproterenol-induced cardiotoxicity in albino rats. Cardiotoxicity was induced in rats by subcutaneous injection of ISO (85 mg/kg bwt) into adult albino rats and treated with the extract (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The antioxidants act through the transfer of hydrogen atoms and by transfer of electrons or chelating of metals [29,30]. The LLFPME showed strong DPPH scavenging activity, ferric reducing antioxidant power and total antioxidant capacity; which compared favourably with the standard drugs used and are consistent with earlier studies [28,29,31,32]. Olarewaju et al [32] reported that total antioxidant capacity of a vegetable is primarily due to the presence of flavonoids and related polyphenols while ferric reducing antioxidant power of selected plant leaves were dose dependent.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The antioxidants act through the transfer of hydrogen atoms and by transfer of electrons or chelating of metals [29,30]. The LLFPME showed strong DPPH scavenging activity, ferric reducing antioxidant power and total antioxidant capacity; which compared favourably with the standard drugs used and are consistent with earlier studies [28,29,31,32]. Olarewaju et al [32] reported that total antioxidant capacity of a vegetable is primarily due to the presence of flavonoids and related polyphenols while ferric reducing antioxidant power of selected plant leaves were dose dependent.…”
Section: Discussionsupporting
confidence: 89%
“…Olarewaju et al [32] reported that total antioxidant capacity of a vegetable is primarily due to the presence of flavonoids and related polyphenols while ferric reducing antioxidant power of selected plant leaves were dose dependent. Fajobi et al [29] and Morakinyo et al [31] also reported dose dependent activities of Pterocarpus mildbraedii and Aframomum melegueta leaves respectively on DPPH and H2O2 radicals, TAC and FRAP.…”
Section: Discussionmentioning
confidence: 94%
“…The significance of this study is also centered on the need to establish an easily accessible natural remedy for the prophylaxis of several cardiovascular diseases. Since recent studies on Moringa oleifera leaves and Aframomum melegueta seeds have shown significant lipid lowering effect [3,4], there is an urgent need to compare the lipid lowering properties of both crude drugs and in turn establish a possible additive, synergistic or antagonistic effect when both crude drugs are used simultaneously.…”
Section: Introductionmentioning
confidence: 99%